Activation of transient receptor potential vanilloid 3 channel (TRPV3) aggravated pathological cardiac hypertrophy via calcineurin/NFATc3 pathway in rats. Issue 12 (9th October 2018) - Zhang, Qianhui; Qi, Hanping; Cao, Yonggang; Shi, Pilong; Song, Chao; Ba, Lina; Chen, Yunping; Gao, Jingquan; Li, Shuzhi; Li, Baiyan; Sun, Hongli
Abstract: Cardiac hypertrophy is a compensatory response to mechanical stimuli and neurohormonal factors, ultimately progresses to heart failure. The proteins of some transient receptor potential (TRP) channels, Ca 2+ ‐permeable nonselective cation channel, are highly expressed in cardiomyocytes, and associated with the occurrence of cardiac hypertrophy. Transient receptor potential vanilloid 3 (TRPV3) is a member of TRP, however, the functional role of TRPV3 in cardiac hypertrophy remains unclear. TRPV3 was elevated in pathological cardiac hypertrophy, but not in swimming exercise‐induced physiological cardiac hypertrophy in rats. TRPV3 expression was also increased in Ang II–induced cardiomyocyte hypertrophy in vitro, which was remarkably increased by carvacrol (a nonselective TRPV channel agonist), and reduced by ruthenium red (a nonselective TRPV channel antagonist). Interestingly, we found that activated TRPV3 in Ang II–induced cardiomyocyte hypertrophy was accompanied with increasing intracellular calcium concentration, promoting calcineurin, and phosphorylated CaMKII protein expression, and enhancing NFATc3 nuclear translocation. However, blocking or knockdown of TRPV3 could inhibit the expressions of calcineurin, phosphorylated CaMKII and NFATc3 protein by Western blot. In conclusion, the activation of TRPV3 aggravated pathological cardiac hypertrophy through calcineurin/NFATc3 signalling pathway and correlated with the protein expression levels of calcineurin, phosphorylated CaMKII and NFATc3, revealing that TRPV3 might be a potential therapeutic target for cardiac hypertrophy.